American physician perceptions of direct-to-consumer advertising: A qualitative study. (July 2013) - Germeni, Evi; Orizio, Grazia; Nakamoto, Kent; Wunsch, Martha; Schulz, Peter J
Abstract : Although scientific evidence concerning harms and benefits of direct-to-consumer advertising (DTCA) is constantly growing, there is a paucity of published research focusing on gaining a better understanding of the perceptions and experiences of involved parties. This gap in the literature becomes even more salient when it comes to the indirect target audiences of DTCA, such as healthcare providers. This study explores American physician perceptions of prescription drug advertising, while elucidating the perceived impact of DTCA in a US context. Our results suggest that 15 years after the introduction of DTCA, physician concerns about its impact on the doctor–patient relationship persist. Negative effects of DTCA include patient acquiring a false sense of autonomy; requests for unnecessary or more expensive drugs; exaggerated perception of advertised drugs' side effects; as well as additional workload and time commitment. Nevertheless, DTCA is also viewed as a stimulus for 'opening communication opportunities' with the patient. Results of this study can be used to inform the dialogue not only in the United States, but also in other countries where efforts are being made to reduce restrictions on DTCA.